ISSUES AND CHALLENGES IN THE APPLICATION OF SPORTS SCIENCE IN THE ASPECT OF PHYSICAL FITNESS WITHIN THE COACHING PROCESS OF UNDER-17 FOOTBALL IN SAMARAHAN - Jidi, Mohd Izdihar Qaedi; Karim, Zulakbal Abdul; Mohamed, Abdul Rahaman (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study examines the issues and challenges faced by under-17 football coaches in Samarahan in applying sports science in the coaching process, specifically in terms of physical fitness. Using a qualitative approach through semi-structured interviews with five active coaches, supplemented by observations and document reviews, this study reveals several key constraints such as the lack of formal educational background in sports science, an unstructured coaching pathway based primarily on experience, limited access to professional training courses and relevant academic resources, and a high dependence on informal learning. These constraints result in inconsistent and less effective application of scientific principles in training, which undermines the quality of youth athlete development. The study emphasises the urgent need for a practical, contextual, and continuous model for the application of sports science that can support grassroots coaches in enhancing their skills and training effectiveness. By integrating relevant theoretical frameworks, namely Grounded Theory (Strauss & Corbin, 1990), the Long-Term Athlete Development (LTAD) model (Balyi et al., 2013), and the Youth Physical Development (YPD) model (Lloyd & Oliver, 2012), this research situates its findings within broader academic discourse. The implications of this study are critical for strengthening coaching development, aligning with Malaysia’s National Football Development Programme (NFDP), and enhancing youth football performance.